Inclusive Islamic Education in the Framework of Inter-Religious Harmony: A Study of Mohammad Talbi's Thoughts - Gaffar, Abdul; Falah, Riza Zahriyal; Syarif, Zainuddin (EDUKASIA, 2022)
The purpose of writing this article is to present a concept of inclusive Islamic education by showing Muslim and Christian relations in the spectrum: “A Common Word” which has a connotative meaning that everything is equal, balanced, and level. Using the study method can reveal the results of the study on the thoughts of Mohammad Talbi. First, it touches on the range of modern Islamic issues and religious issues in general in the context of intra-Islamic relations and the relationship between Islam and other religions, particularly the relationship between Muslims and Christians. Second, building a paradigm of peace among adherents of the "Ibrahim faith" and building awareness that we and followers of other religions are one big family, namely the Ibrahim family (Millah Ibrahim) who can create a world of peace and harmony in diversity. The third ideas of Mohammad Talbi as an instrument in the process of understanding or constructing the historical-sociological-humanist perspective approach. The fourth is the relevance of the Islamic education model.